Meat Science Lexicon* - Dennis L.Seman; Dustin D.Boler; C. ChadCarr; Michael E.Dikeman; Casey M.Owens; Jimmy T.Keeton; T. DeanPringle; Jeffrey J.Sindelar; Dale R.Woerner; Amilton S.de Mello; Thomas H.Powell (Meat and Muscle Biology, 2018)
The American Meat Science Association (AMSA) became aware of the need to develop a Meat Science Lexicon for the standardization of various terms used in meat sciences that have been adopted by researchers in allied fields, culinary arts, journalists, health professionals, nutritionists, regulatory authorities, and consumers. Two primary categories of terms were considered. The first regarding definitions of meat including related terms, e.g., “red” and “white” meat. The second regarding terms describing the processing of meat. In general, meat is defined as skeletal muscle and associated tissues derived from mammals as well as avian and aquatic species. The associated terms, especially “red” and “white” meat have been a continual source of confusion to classify meats for dietary recommendations, communicate nutrition policy, and provide medical advice, but were originally not intended for those purposes. In this paper, processed meat is defined in terms of the actions of processing, i.e., “minimal processing” and “further processing”; the main distinction being whether additional ingredients were included or excluded. Meat processing has become more complex as technologies have improved, and the official words to describe them have not remained current.